Membrane-Peptide Interactions From Basics to Current Applications - Santos, Nuno C.; Gonçalves, Sónia (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book summarizes the importance of peptide-membrane interactions, mostly aiming at developing new therapeutic approaches. The experimental and computational methodologies used to investigate such interactions reveal the evolution of existing biophysical methodologies, shedding some light on potential applications of peptides, as well as on the improvement of their design. Understanding the determinants for peptide-membrane interactions may also improve the knowledge of membrane functions such as the membrane transport, fusion, and signaling processes, contributing to the development of new agents for highly relevant applications ranging from disease treatment to food technology.